Arsagermene, a compound with an –AsGe double bond. Issue 78 (14th August 2018) - Lee, Vladimir Ya.; Kawai, Manami; Gapurenko, Olga A.; Minkin, Vladimir I.; Gornitzka, Heinz; Sekiguchi, Akira
Abstract : Arsagermene, a stable compound featuring an AsGe double bond, was synthesized, isolated, and structurally characterized for the first time. Abstract : The first compound featuring an AsGe double bond, arsagermene Mes*AsGe(SiMe t Bu2 )2, was synthesized, isolated and fully characterized. Crystallographic studies revealed that arsagermene has a planar GeAs bond of 2.2731(8) Å, which is notably shorter than the standard Ge–As single bond. The double bond character of arsagermene was further supported by computational data.